Determinan Keputusan Pembelian Produk Skincare The Originote (Studi Pada Pengguna Aplikasi TikTok) - Silvia Anggraeni; Ajat Sudrajat (Jurnal Manajemen DIVERSIFIKASI, 2025)
The purpose of this study is to examine the effect of Content Marketing, Live Streaming, andElectronic Word of Mouth (eWOM) on purchasing decisions for The Originote skincareproducts. The method used is quantitative, with the type of data, namely primary data with aquestionnaire as a form of data collection. The analysis method used by this research isPartial Least Square (PLS) SEM with the help of SmartPLS 4.0 software. The population inthis study are users or consumers of The Originote products who use TikTok. The samplingtechnique used, namely purposive sampling and a sample size of 100 was obtained using theLameshow technique. The results of this study found that Content Marketing (X1) and LiveStreaming (X2) did not significantly affect the Purchase Decision (Y) of The OriginoteSkincare Products. Electronic Word of Mouth (eWOM) (X3) positively and significantlyinfluences the Purchasing Deciusion (Y) of The Originote Skincare Product